2016
DOI: 10.1515/ract-2016-2614
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and hydrolysis of Np(V) in dilute to concentrated alkaline NaCl solutions: formation of Na–Np(V)–OH solid phases at 22 °C

Abstract: Abstract:The solubility of Np(V) was investigated at T = 22 ± 2 °C in alkaline NaCl solutions of different ionic strength (0.1-5.0 M). The solid phases controlling the solubility at different -log 10 m H +(pH m ) and NaCl concentration were characterized by XRD, quantitative chemical analysis, SEM-EDS and XAFS (both XANES and EXAFS). Aqueous phases in equilibrium with Np(V) solids were investigated for selected samples within 8.9 ≤ pH m ≤ 10.3 by UV-vis/NIR absorption spectroscopy. In 0.1 M NaCl, the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Solubility of Np(V) in the presence of borate In the latter case either NpO 2 OH(am) or ternary Na/Mg-Np(V)-borate(cr) solid phases were used as the "starting material". Np(V) solubility data reported in the literature for borate-free systems under analogous pH m and ionic strength conditions are appended to the figure for comparison purposes, [38][39][40] as well as the solubility curves of NpO 2 OH(am,fresh) calculated with the thermodynamic data selected in the NEA-TDB. 16 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Solubility of Np(V) in the presence of borate In the latter case either NpO 2 OH(am) or ternary Na/Mg-Np(V)-borate(cr) solid phases were used as the "starting material". Np(V) solubility data reported in the literature for borate-free systems under analogous pH m and ionic strength conditions are appended to the figure for comparison purposes, [38][39][40] as well as the solubility curves of NpO 2 OH(am,fresh) calculated with the thermodynamic data selected in the NEA-TDB. 16 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is also interesting to compare the length of characteristic bonds of mononuclear aqua and monohydroxo complexes, as such species are present in the pH > 9 regime 52 where [(NpO 2 ) 2 (OH)] + might exist, because this comparison could be helpful for an experimental identification of the Np(V) diactinyl monohydroxo complex. The structures of the Np(V)−pe dimers are distinguished from those of the favorable An(VI) diactinyl monohydroxo complexes of the pa type by different Np�O actinyl bond lengths of about 184 and 187 pm in the essentially linear neptunyl units (Table 2).…”
Section: Inorganicmentioning
confidence: 99%
“…This fact gave cause to some debates as recently summarized in Petrov et al and is reflected by the large uncertainty values of the current NEA-TDB data. 19 The current NEA-TDB database provides recommended solubility constants for only one Np(V) hydroxide compound that is relevant for the H−Na−Cl−OH−H 2 O system: NpO 2 OH(am). Due to the great thermodynamic stability of the redox neighbors Np(IV) and Np(VI), the modeled predominance field of NpO 2 OH(am) and, hence, of solid Np(V) ends at about pH m ≈ 11 as indicated by the red dotted line in Figure 3b.…”
mentioning
confidence: 99%
“…Recent solubility investigations performed with Np­(V) hydroxides set another priority. They showed that (poly)­crystalline M–Np­(V)–OH solid phases (M = Na and Ca) significantly enhance the thermodynamic stability of Np­(V) in alkaline NaCl and CaCl 2 solutions but lacked detailed structural models of the solubility controlling solid phases. Herein, we report on the successful combination of a comprehensive structural and thermodynamic investigation of two different Na–Np­(V)–OH solid phases. Synthesis, crystal structures, and the results of systematic solubility studies of the hitherto unknown Na 0.5 [NpO 2 (OH) 1.5 ]·0.5H 2 O (I) and the previously reported Na­[NpO 2 (OH) 2 ] (II) are discussed.…”
mentioning
confidence: 99%
See 1 more Smart Citation